Analisis Penggunaan Total Quality Control Sebagai Upaya Meminimalisasi Resiko Kerusakan Produk Keripik Singkong Madani - Mariyanti, Mariyanti; Langga, Lambertus; Tanusi, Gabriel (Program Studi Manajemen Universitas Flores, 2021)
The purpose of this study is to find out the Total Quality approach Control as an effort to minimize the risk of product damage to Madani Cassava chips and factors that cause product quality failure on Madani Kripik Singkong. Methods used in this study is a statistical analysis that uses control map P namely: a) control map p consisting of: 1) calculate the percentage of damage, 2) central line, 3) upper control line, 4) lower control line; b) 100 percent flawed control diagram inspection, consisting of: 1) calculating the center line, 2) calculating the control limit above, 3) calculate the lower limit of control, causation and keizen. The results of this study show that by using a control map P average product damage P 0.0413, upper control limit or UCL of 0.0532, and the lower control limit or LCL of 0.0294 of the calculation result control map P showing Total Qualiti Control or quality control the product is said to be good, based on the results of the analysis using a diagram of the cause of factors that cause product quality failure are human, machine, method and environment in analysis using kaizen method indicates that supervision must be continued to maintain the quality of products by monitoring employee performance, providing clear instructions employees so that human methods and factors can be carried out by well, for environmenta lfactors, namely animating the warehouse and cleaning the warehouse at all times so that dirt and dust are not mixed with raw materials while the machine factor is to supervise and maintain the machine in order to the engine remains optimal.